Trolleys, Transplants and Inequality: An Egalitarian Proposal. - Baumann, Peter (Erkenntnis, 2022)
This paper deals with the core version of the Trolley Problem. In one case (Trolley) many people favor an act (throwing a switch) which will bring about the death of one person but save five other persons (rather than letting five die and one go on living). In another case (Transplant) most people would refuse to "sacrifice" one person in order to save five other lives (rather than letting five die and one go on living). Since the two cases seem similar in all relevant respects, we have to explain and justify the diverging verdicts. Since I don't find current proposals of a solution convincing, I propose an alternative one according to which (Transplant)—but not (Trolley)—violates two forms of equality. I also test the underlying egalitarian principle against other cases. I argue that it offers a good explanation and also a normative justification of our intuitive verdicts about the cases.